KOMPONEN-KOMPONEN PROFESIONALISME GURU - Addini, Ichwanul Hakim; rayya, muhammad; nurcahyo, hengki fajar; hasan , muhammad rafi; rodhiyana, mu'allimah (Ilma Jurnal Pendidikan Islam, 2024)
Abstract This article discusses the components of teacher professionalism. In this article, it is revealed that teacher professionalism has a very important role in determining the quality of education in the school itself. The aim of this research is to determine the performance of a teacher in an educational institution. Through this article we will find out the components of a teacher's professionalism in school. This research method comes from several collections of previous scientific work which were used to answer various research problems, using journals, and observing the environment. Then the discussion will continue by understanding the components of teacher professionalism, such as the teacher code of ethics and teacher work ethic. Teachers have an important role in improving the quality of education and are responsible for organizing educational activities. The results of this research should enable all parties who contribute to the world of education, especially teachers, to be able to apply these components so as to gain useful knowledge. Keywords: Components, Professionalism, Teachers Abstrak Artikel ini membahas tentang komponen-komponen profesionalisme guru. Pada artikel ini di ungkapkan bahwa profesionalisme guru memiliki peran yan sangat penting untuk menentukan mutu pendidikan dalam sekolah itu sendiri. Tujuan dari penelitian ini adalah untuk mengetahui kinerja seorang guru di dalam instansi pendidikan, melalui artikel ini kita akan mengetahui komponen-komponen profesionalisme seorang guru di sekolah . Metode penelitian ini bersumber dari beberapa kumpulan hasil karya ilmiah sebelumnya yang digunakan untuk menjawab berbagai permasalahan penelitian, menggunakan jurnal, serta mengamati lingkungan. Lalu pembahasan akan dilanjutkan dengan memahami komponen-komponen profesionalisme guru seperti, kode etik guru, dan etos kerja guru. Guru mempunyai peranan penting dalam meningkatkan mutu pendidikan dan bertanggung jawab dalam penyelenggaraan kegiatan pendidikan. Hasil dari penelitian ini hendaknya bagi semua pihak yang berkontribusi dalam dunia pendidikan khususnya bagi seorang guru dapat mengaplikasikan komponen-komponen tersebut sehingga mendapatkan ilmu yang bermanfaat. Kata Kunci: Komponen, Profesionalisme, Guru